2013
DOI: 10.1210/jc.2013-1940
|View full text |Cite
|
Sign up to set email alerts
|

Medullary Thyroid Cancer Secreting Carbohydrate Antigen 19-9 (Ca 19-9): A Fatal Case Report

Abstract: High levels of serum Ca 19-9 could be considered a marker of the dedifferentiation of MTC and disease aggressiveness, but additional data on the association between Ca 19-9 and advanced MTC are required to confirm this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Recently we observed a peculiar case of aggressive MTC in a young patient with MEN2A who rapidly died of neoplasia (23). High serum levels of Ca 19.9, which is typically considered a gastrointestinal tumor marker (26), were present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we observed a peculiar case of aggressive MTC in a young patient with MEN2A who rapidly died of neoplasia (23). High serum levels of Ca 19.9, which is typically considered a gastrointestinal tumor marker (26), were present.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the case of a 56-year-old woman with MEN2B and high serum levels of Ca 19.9 and the case of a young man with MEN2A who exhibited high and progressively increasing serum levels of Ca 19.9 have been reported (22,23) and the possibility that high levels of serum Ca 19.9 could be a prognostic factor of poor prognosis has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in view of its abnormal increased expression level in common pancreatic cancer; CA19-9 has been used as a diagnostic marker to differentiate pancreatic cancer from pNETs (15,16). However, few previous studies have demonstrated that CA19-9 may be used as a prognostic biomarker in neuroendocrine tumors (17,18). For example, Elisei et al (17) reported a case of multiple endocrine neoplasia type 2B with significant elevation of CA19-9 expression levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, few previous studies have demonstrated that CA19-9 may be used as a prognostic biomarker in neuroendocrine tumors (17,18). For example, Elisei et al (17) reported a case of multiple endocrine neoplasia type 2B with significant elevation of CA19-9 expression levels. The patient experienced rapid disease progression and survived for only a short period, indicating that CA19-9 may be a biomarker of aggressiveness (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation